Design of Compact Particle Detector System Using FPGA for Space Particle Environment Measurement - K. Ryu; D. S. Oh; S. J. Kim; H. J. Kim; J. J. Lee; G. H. Shin; D. H. Ko; K. W. Min; J. A. Hwang (Journal of Astronomy and Space Sciences, 2007)
We have designed a high resolution proton and electron telescope for the detection of high energy particles, which constitute a major part of the space environment. The flux of the particles, in the satellite orbits, can vary abruptly according to the position and solar activities. In this study, a conceptual design of the detector, for adapting these variations with a high energy resolution, was made and the performance was estimated. In addition, a parallel processing algorithm was devised and embodied using FPGA for the high speed data processing, capable of detecting high flux without losing energy resolution, on board a satellite.